The amygdala's response to face and emotional information and potential category-specific modulation of temporal cortex as a function of emotion - White, Stuart F.; Adalio, Christopher; Nolan, Zachary T.; Yang, Jiongjiong; Martin, Alex; Blair, James R. (Frontiers in Human Neuroscience, 2014)
The amygdala has been implicated in the processing of emotion and animacy information and to be responsivity to novelty. However, the way in which these functions interact is poorly understood. Subjects (N= 30) viewed threatening or neutral images that could be either animate (facial expressions) or inanimate (objects) in the context of a dot probe task. The amygdala showed responses to both emotional and animacy information, but no emotion by stimulus-type interaction; i.e., emotional face and object stimuli, when matched for arousal and valence, generate comparable amygdala activity relative to neutral face and object stimuli. Additionally, a habituation effect was not seen in amygdala; however, increased amygdala activity was observed for incongruent relative to congruent negative trials in second vs. first exposures. Furthermore, medial fusiform gyrus showed increased response to inanimate stimuli, while superior temporal sulcus showed increased response to animate stimuli. Greater functional connectivity between bilateral amygdala and medial fusiform gyrus was observed to negative vs. neutral objects, but to fearful vs. neutral faces. The current data suggest that the amygdala is responsive to animate and emotional stimuli. Additionally, these data suggest that the interaction between the various functions of the amygdala may need to be considered simultaneously to fully understand how they interact. Moreover, they suggest category-specific modulation of medial fusiform cortex as a function of emotion.